Molecular and histopathological landscape of 131 meningiomas: a retrospective institutional study with insights from cIMPACT-NOW - Ali, Rola H.; Hassan, Abdulaziz; Jarkhi, Hussain H.; Alshawish, Abdullah; Almanabri, Mohamad; Alhalabi, Obada; Alsaber, Ahmad R.; Ali, Nawal Y.; Abdelnabi, Ehab; Mohammed, Eiman M. A.; Jama, Hiba; Almarzooq, Ammar; et al. (Frontiers in oncology, 2025)
BackgroundPrognostication in meningiomas has traditionally relied on histopathological grading, which has inherent limitations, including interobserver variability, intratumoral heterogeneity, and inconsistent correlation with clinical behavior. While molecular profiling enhances diagnostic precision and risk stratification, it is not yet routinely adopted in clinical practice. To date, no molecular data on meningiomas have been published from our country. This study aims to address this gap by characterizing the molecular landscape of meningiomas at our institution, incorporating insights from recent cIMPACT-NOW updates.MethodsWe retrospectively analyzed consecutive 131 meningiomas that underwent molecular sequencing at our institution between 2021 and 2023. Tumors were classified according to the latest WHO criteria. Next-generation sequencing (NGS) was performed using the Oncomine Comprehensive Assay, a targeted panel for solid tumors. Molecular findings were correlated with clinicopathological parameters.ResultsThe cohort included 84 females and 47 males (median age: 51 years; range: 2-79). Tumor locations included the cerebral convexity (45.8%), skull base (38.2%), posterior fossa (3.1%), and spine (5.3%), with 7.6% being multifocal. CNS WHO grade 2 tumors were most common (58%), followed by grade 1 (35%) and grade 3 (7%). NF2 alterations (35%) were the most frequent, occurring across all grades but more prevalent in grades 2 and 3. Genotype (p = 0.004) and WHO grade (p = 0.002) were significantly associated with tumor location: NF2 alterations predominated in convexity and spine, while TRAKLS mutations (TRAF7, AKT1, KLF4, SMO) were enriched in lower-grade skull base tumors. High-risk homozygous CDKN2A/B deletions were identified in one grade 3 tumor, with hemizygous deletions, unexpectedly, in three grade 2 tumors.ConclusionThis study provides regional insight into the molecular landscape of meningiomas in our population. While routine molecular profiling adds value to classification and prognostication, broader implementation may be limited by cost and panel coverage constraints.
Gesehen am 28.01.2026